KETERWAKILAN PEREMPUAN ANTARA KUANTITAS DAN KUALITAS DI DPRD KOTA PALEMBANG PERIODE 2019-2024 - Tribuana, Julianto Indra; Izomiddin, Izomiddin; Waty, Reni Rentika (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to determine the quantity and quality of women members in the Palembang City DPRD for the 2019-2024 period. This research uses the political theory of presence from Anne Phillips, where this theory can answer and solve problems related to women's representation in the legislature, and emphasize the importance of women's presence and participation in the political process. And also this study uses Hanna Pitkin's representation theory, where this theory answers their ability to represent and fight for the broader interests of women. The research method used is qualitative method, using observation, interview, and documentation techniques as data collection. The results showed that related to quantity, the presence of women in the Palembang City DPRD, they already exist in the legislative section, representative of women in Palembang City, but related to the 30% women's representation quota can be said to be unfulfilled. While related to quality For approximately three years, female legislative members of the Palembang City DPRD have done a good job in dealing with women's issues. During this period, local regulations have been made that specifically deal with women's issues. However, it is hampered by the budget that has been set, so that it does not cover the maximum, for policies that support women, such as gender-responsive budgets.